Endogenous sensitizer of beta-adrenergic receptors (ESBAR) and its analogs (review) - Tsirkin, Victor; Nozdrachev, Alexander; Sizova, Elena; Polezhaeva, Tatyana; Khlybova, Svetlana; Morozova, Marina; Trukhin, Andrew; Korotaeva, Julia; Khodyrev, Grigory (Journal of Cardiology and Cardiovascular Medicine, 2018)
The results of the 20 years studies of the presence in blood serum and other body fluids of endogenous modulators of adrenergic and M-cholinergic impact as a component of humoral link of autonomic nervous system. The article is devoted to the endogenous sensitizer of beta-adrenergic receptor (ESBAR) - water-soluble low molecular weight substances, analogs of which are histidine, tryptophan, tyrosine, mildronat and preductal. It is shown, that separate dilutions of human serum and animal (as a source of ESBAR) and analogs of ESBAR ways to enhance the effectiveness of activation of beta-adrenoceptors (AR) of smooth muscle (uterus, coronary and renal arteries, trachea, stomach), myocardium, erythrocytes and platelets (respectively influenced of histidine and tryptophan). It is reported that content of ESBAR in human serum (according to the titers of its dilution) depends on the sex and the presence of somatic diseases, and at women are also on the stage of reproduction and obstetric complications It is discussed possible mechanisms of ESBAR action, its physiological role, including as a component of beta-adrenoceptor inhibitory mechanism for myometrium, as well as the prospect of the use of analogs of ESBAR, including for the prevention of preterm labor, and for the treatment of bronchial asthma, coronary heart disease, hypertension and heart failure.